Handbook of Justice Research in Law - Sanders, Joseph.; Hamilton, V. Lee. (Springer US, 2001)
JusticeỚ a word of great simplicity and almost frightening scope. When we were invited to edit a volume on justice in law, we joked about the small topic we had been assigned. Often humor masks fear, and this was certainly one of those times. Throughout the project, we found daunting the task of covering even a fraction of the topics that usually fall under the umbrella of justice research in law. Ultimately, the organization of the book emerged from the writing of it. Our introductory chapter provides a road map to how the topics weave together, but as is so often the case it was written last, not ?rst. It was only when we had chapters in hand that we began to see how the many strands of justice research might be woven together. Chapters 2Ớ<U+001c>4 on the basic forms of justiceỚ procedural, retributive, and distributiveỚ are the lynchpin of the volume; they provide the building blocks that permit us to think and write about each of the other substantive and applied chapters in terms of how they relate to the fundamental forms of justice. In the large central section of the volume (Chapters 5Ớ<U+001c>9), the contributors address many ways in which the justice dimensions relate to one another. Most important for law is the relationship of perceptions of procedural justice and the two types of substantive justiceỚ retributive and distributive.